PEMBELAJARAN SEJARAH YANG EFEKTIF DI SMA NEGERI 1 MLATI SLEMAN - Inna Felinda; Sugiyono Sugiyono (ISTORIA: Jurnal Pendidikan dan Sejarah, 2018)
This study aimed to determine: (1) the application of learning methods, (2) the application of learning models, (3) the application of learning evaluation, (4) factors that support effective history learning, (5) factors that inhibit effective historical learning, (6) the absorption rate of students in learning history, and (7) the role of teachers in learning history of SMA Negeri 1 Mlati Sleman.This research is a qualitative. Key informant in this research were Headmaster, Deputy Headmaster of Curriculum Field, Teachers of History Study Course, and Students of IPS Department and IPA Class XI. Data collection techniques included interviews, observation, and documentation. Data validity used data triangulation. Data analysis technique used Miles and Huberman analysis model that was causal network. To be able to describe the meaning of relationships between factors in this study, using the method of fishbone diagram was used.The results showed that: (1) history learning of SMA Negeri 1 Mlati Sleman, included activities to select, establish, develop methods to achieve the desired teaching outcomes. The selection, determination, and development of this method were based on existing teaching conditions especially on historical learning. (2) One of the historical learning models used was images and video that were done so that images could be sorted into a logical sequence. (3) Evaluation of learning has been prepared at the beginning or time of programming of the semester except for evaluation or the final examination of the school was planned or taken preparation time of daily evaluation of each sub subject. For evaluation there were a written test, oral test (question and answer). (4) Factors that support the learning was that the learning strategy that was delivered could be received well by students and foster interest in student’s learning, because the interest was very influential in the process and learning outcomes. (5) Factors that hamper the learning of history included the diffent ability of students so that an individual learning approach was required for each student. Other obstacles are resources and learning tools such as history labs that had not been owned. (6) The absorption rate of students in learning history was closely related to students' understanding. In the learning process, each individual student had different abilities in understanding what he or she was learning. (7) The role of teachers in learning history included to providing motivation to students to be more enthusiastic in learning and stablishing good communication between teachers and students.Keywords: effective history learning, SMA N 1 Mlati